Critical Reflections on Reimbursement and Access of Advanced Therapies - Simoens, Steven; De Groote, Katrien; Boersma, Cornelis (Frontiers in Pharmacology, 2022)
BACKGROUND: The health economic literature has questioned the cost-effectiveness and affordability of advanced therapies, proposed adjustments to value assessment frameworks, and discussed the use of outcome-based managed entry agreements and staggered payments in the last few years. The aim of this manuscript is to conduct a critical reflection on assessment criteria and access conditions for reimbursement of advanced therapies. METHODS: A narrative review of the peer-reviewed literature and grey literature was conducted in April 2021 by searching PubMed; Google Scholar; policy and legislative documents; websites of health technology assessment agencies, advanced therapy organisations, governmental advanced therapy innovation programmes, consultancy agencies; ISPOR conference abstracts and presentations. RESULTS: Based on the available evidence, this manuscript argues that: a) advanced therapies can be cost-effective at high prices set by manufacturers; b) the economic evaluation framework adopted by many payers under-values these products; c) advanced therapies can be affordable and may not require spread payments; d) outcome-based managed entry agreements are theoretically attractive, but challenging in practice; e) the cost-effectiveness of advanced therapies depends on the outcome-based managed entry agreement and payment approach; f) there is a role for collaborations between countries to manage reimbursement and access of advanced therapies. CONCLUSIONS: This manuscript shows that there is no single approach to reimbursement and access of advanced therapies. Instead, we support a more tailored assessment of health economic aspects of advanced therapies, which considers the heterogeneity of these products and their target populations.